PENGARUH INTELLECTUAL CAPITAL TERHADAP BUSINESS PERFORMANCE DENGAN PENDEKATAN BALANCED SCORECARD PADA PERUSAHAAN MANUFAKTUR BERSKALA BESAR DI SURABAYA - Nurul Kompyurini (InFestasi, 2010)
The  purpose of this empirical research is to examine influenced the three elements of intellectual capital that are human capital, structural capital, and customer capital  with business performance.Data used for this research was collected from human resources development, financial, marketing, and  R D manager. Data collected by contact person. 37 questionnaires were sent to managers from big scale manufactur enterprises in Surabaya. Analysis was  conducted using Linear Multiple Regression with SPSS 11.0 softwares.The main conclusions from this  research are that : human capital, structural capital, and customer capital  simultaneously  have  positive  and significant influence with business performance    human capital has positive  and significant influence with business performance,  structural capital has positive  and significant influence with business performance, and customer capital has positive  and significant influence with business performance.